Commute UX: Voice Enabled In-car Infotainment System - Tashev, Ivan; Seltzer, Mike; Ju, Y. C.; Wang, Ye-Yi; Acero, Alex (Mobile HCI '09: Workshop on Speech in Mobile and Pervasive Environments (SiMPE), 2009)
Voice enabled dialog systems are well suited for in-car applications. Driving is an eyes-busy and hands-busy task and the only wideband communication channel left is speech. Such systems are in the midst of a transformation from a cool gadget to an integral part of the modern automobile. In this paper we highlight the major requirements for an in-car dialog system including usability during conditions of cognitive load, efficiency though multimodal user interface, dealing with locations, handling the noise in the car with better sound capture and robust speech recognition. We then present Commute UX, our prototype multi-modal dialog system for in-car infotainment system.